Supraventricular Tachycardia Induced by Cisplatin in a Patient with Breast Cancer: A Case Report - Laksono, Sidhi; Kusharsamita, Hillary (http://dharmais.co.id/, 2024)
Introduction: Cisplatin is one of the most extensively used chemotherapeutic agents for treating many malignancies. Cisplatin chemotherapy, on the other hand, is linked to cardiotoxicity, which may vary from silent arrhythmias to heart failure to sudden cardiac death. In this article, we describe a case of supraventricular tachycardia induced by cisplatin in a breast cancer patient. Case Presentation: Our patient had no history of heart disease and had SVT during cisplatin administration. This condition resolved when the infusion was stopped and amiodarone was administered intravenously. The electrolyte levels were within the usual range. No abnormalities were detected on her echocardiography imaging. Primary cardiotoxicity from cisplatin was subsequently determined to be this patient's root cause of SVT. The patient also had an excellent response to the subsequent cycles of treatment. Conclusions: It is important to note that cisplatin therapy is associated with cardiac toxicity. Arrhythmias such as SVT have been associated with chemotherapy drugs. Hence the ECG has to be closely monitored during cisplatin administration. In addition, An ECG and echocardiogram should be done regularly to rule out the possibility of a secondary form of chemotherapy-induced arrhythmia.